Security and trust management : 15th International Workshop, STM 2019, Luxembourg City, Luxembourg, September 26-27, 2019, Proceedings /: 15th International Workshop, STM 2019, Luxembourg City, Luxembourg, September 26-27, 2019, Proceedings. (2019) - Unknown
No abstract available